Inhibition of phytopathogens by certain strain of Azotobacter chroococcum under in vitro conditions - K. LAKSHMINARAYANA, SUNITA SUNEJA and (Indian Phytopathology, 2002)
Siderophore positive and negative cultures of Azotobacter chroococcum were tested for inhibition studies. Different inhibition patterns were seen with fungal and bacterial phytopathogens. A methyl ammonium chloride resistant mutant, Mac 21, inhibited all phytopathogens excepting one fungal pathogen, Neovossia indica, which was, however, stimulated by all A. chroococcum culture supernatants tested except that of 100 and 54. Two mitomycin derived siderophore negative mutants Ml and M2 caused very low stimulation of Neovossia indica compared to their Fe- parent A. chroococcum 111. Antagonism of plant pathogens was seen with both Fe- and Fe+ culture supernatants of A. chroococcum although the degree of antagonism was different.